Religion and Ethical Attitudes toward Accepting a Bribe: A Comparative Study - McGee, Robert W. (Religions, 2015)
This study presents the results of an empirical study of ethical attitudes toward bribe taking in six religionsChristianity, Islam, Buddhism, the Baha'i faith, Hinduism, and Judaism. The paper begins with a discussion of the theoretical and empirical literature on the subject. The empirical part of the study examines attitudes toward accepting bribes in 57 countries from the perspectives of six religions using the data from Wave 6 (2010-2014) of the World Values Survey. The sample population is more than 52,000. More than a dozen demographic variables were examined. The study found that attitude toward bribe taking does differ by religion.